ANALISIS RASIO KEUANGAN METODE RBBR DALAM MENGUKUR TINGKAT KESEHATAN BANK PADA BANK UMUM SYARIAH (BUS) PERIODE 2013-2020 - Elsa Elsa (JAAKFE UNTAN (Jurnal Audit dan Akuntansi Fakultas Ekonomi Universitas Tanjungpura), 2023)
This research has a purpose that is: 1. To analyze tha bank’s health level with the financial ratio of the Risk Based Bank Rating (RBBR) method at the BUS period 2013-2020, 2. To determine the difference in the bank’s health level with the financial ratio of Risk Based Bank Rating (RBBR) method at the BUS period 2013-2020. This research uses comparative analysis methods. The classic assumptions used in this research are the normality tes, homogeneous test, while the difference test used the kruskal wallis test. The result of the analysis with the RBBR method indicate that BUS from 2013-2020 has a condition of the bank’s health level in a composite rating of 3 with a value of 64% which means healthy enough, while based on the calculation of different test, seven banks that are used as samples in this study there is a difference from the ratio of NPF, ROA,BOPO and CAR because they have a significant difference of < 0,05 while for the FDR ratio there is no difference from the seven banks because the significant value is > 0,05.